A bi-objective bi-level signal control policy for transport of hazardous materials in urban road networks. (January 2016) - Chiou, Suh-Wen
Highlights: A bi-objective bi-level signal control model for hazardous materials is proposed. A least maxi-sum risk model with signal delay is considered. A bundle and bounding strategy is presented. Numerical comparisons are made with risk-averse models. Trade-offs between public risk and travel cost are numerically investigated among various risk-averse models. Abstract: A bi-objective bi-level signal control optimization for hazardous material (hazmat) transport is considered to assess trade-offs between travel cost and environment impacts such as public risk exposure. A least maxi-sum risk model with explicit signal delay is presented to determine generalized travel cost for hazmat carriers. Since the bi-level signal control problem is generally a non-convex program, a bundle method using generalized gradients is proposed. A bounding strategy is developed to stabilize solutions of the bi-level program and reduce relative gaps between iterations. Numerical comparisons are made with other risk-averse models. The results indicate that the proposed bi-objective bi-level model becomes even amiable to signal control policy makers since provides flexible solutions whilst is acceptable to carriers since takes account of travel delay at signal-controlled junctions. Moreover, the trade-offs between public risk and generalized travel costs are empirically investigated among different risk models with a variety of weights. As a result, the proposed model consistently exhibits highly considerable advantage on mitigation of public risk whilst incurred less cost loss as compared to other alternatives.